2019
DOI: 10.1101/2019.12.17.880070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

sisterless Ais required for activation ofSex lethalin theDrosophilagermline

Abstract: In Drosophila, sex determination in somatic cells has been well-studied and is under the control of the switch gene Sex lethal (Sxl), which is activated in females by the presence of two X chromosomes. Though sex determination is regulated differently in the germline versus the soma, Sxl is also necessary and sufficient for the female identity in germ cells. Loss of Sxl function in the germline results in ovarian germline tumors, a characteristic of male germ cells developing in a female soma. Further, XY (mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…cDNA representing the Pe transcript was identified in early germ cells [Shigenobu et al, 2006], and expression of an early promoter (Pe-GFP) reporter was observed in early first instar larval germ cells [Goyal et al, 2021]. In addition, when the late Sxl protein was specifically tagged, expression was first observed in second instar larvae, after Pe is active, consistent with a need to activate Pe in order to allow production of functional protein from Pm [Goyal et al, 2021].…”
Section: Activation Of Sxlmentioning
confidence: 92%
See 3 more Smart Citations
“…cDNA representing the Pe transcript was identified in early germ cells [Shigenobu et al, 2006], and expression of an early promoter (Pe-GFP) reporter was observed in early first instar larval germ cells [Goyal et al, 2021]. In addition, when the late Sxl protein was specifically tagged, expression was first observed in second instar larvae, after Pe is active, consistent with a need to activate Pe in order to allow production of functional protein from Pm [Goyal et al, 2021].…”
Section: Activation Of Sxlmentioning
confidence: 92%
“…The model of autoregulation in the soma, where the early promoter (Pe) is active only in females to produce a protein that autoregulates the transcript from the maintenance promoter (Pm) is also thought to occur in the germline [Hager and Cline, 1997]. cDNA representing the Pe transcript was identified in early germ cells [Shigenobu et al, 2006], and expression of an early promoter (Pe-GFP) reporter was observed in early first instar larval germ cells [Goyal et al, 2021]. In addition, when the late Sxl protein was specifically tagged, expression was first observed in second instar larvae, after Pe is active, consistent with a need to activate Pe in order to allow production of functional protein from Pm [Goyal et al, 2021].…”
Section: Activation Of Sxlmentioning
confidence: 99%
See 2 more Smart Citations
“…4c). Among those, two are X-encoded transcription factors Cut and SisA, the latter being a known X-dosage sensor in the soma and recently shown to regulate germline expression of Sxl, a known regulator of female germline sexual development (Cline and Meyer 1996;Goyal et al 2020). These genes may also contribute to germline sex determination.…”
Section: Figure 2 Expression Trends In the Germline Clusters And Actmentioning
confidence: 99%